Providing Online Education to Improve Health and Nutrition Knowledge in Security Units during the Pandemic (Covid-19) - Tsani, A. Fahmy Arif; Nugroho, Teddy Wahyu; Ayustaningwarno, Fitriyono; Dieny, Fillah Fithra; Kristiana, Ida (Universitas Aisyah Pringsewu, 2020)
Security Unit (SATPAM) is a profession that demands good endurance. During a pandemic, online education is one way that can be done to provide information about health and nutrition that can improve work performance and body resistance of security guards. This study aims to determine the effectiveness of providing online education to increase knowledge of health and nutrition in a security unit during a pandemic. This research is a quantitative study with a pretest-posttest design which was carried out on 68 security guards at the Diponegoro University campus. Online educational media used via Whatsapp. This research was in the form of providing a nutritional knowledge pretest, nutritional education and nutritional knowledge posttest to see the level of knowledge of the security unit. The pretest and posttest knowledge data analysis used paired t-test if the data distribution was normal and if the data distribution was not normal will use Wilcoxon. The results of statistical analysis showed that there was a significant difference in pretest and posttest nutritional knowledge (p = 0.002), with the median and average value of the Undip security guards’ nutritional knowledge from a median of 72.5 (45-85) to 80 (50-95) with the average of 70.96 before education and after education increased to 75.88. There is an effect of providing online nutrition education on increasing security knowledge of health and nutrition. Abstrak: Satuan Pengaman (SATPAM) adalah salah satu profesi yang menuntut daya tahan tubuh yang baik. Di masa pandemi, edukasi online merupakan salah satu cara yang dapat dilakukan untuk memberikan informasi mengenai kesehatan dan gizi yang dapat meningkatkan performa kerja dan daya tahan tubuh satpam. Penelitian ini bertujuan untuk mengetahui efektivitas pemberian edukasi online untuk meningkatkan pengetahuan kesehatan dan gizi pada satuan pengamanan (satpam) di masa pandemi. Penelitian ini merupakan penelitian kuantitatif dengan rancangan pretest posttest design yang dilakukan pada 68 satpam kampus Universitas Diponegoro. Media edukasi online yang digunakan melalui Whatsapp. Penelitian ini berupa pemberian pretest pengetahuan gizi, edukasi gizi dan posttest pengetahuan gizi untuk melihat tingkat pengetahuan satpam. Analisis data pengetahuan pre dan posttest menggunakan paired t-test apabila distribusi data normal dan wilcoxon apabila distribusi data tidak normal. Hasil analisis statistik menunjukkan bahwa terdapat perbedaan signifikan pengetahuan gizi pre dan posttest (p=0,002), dengan nilai median dan rata-rata terdapat peningkatan pengetahuan gizi satpam Undip dari median 72,5 (45-85) menjadi 80 (50-95) dengan rata-rata 70,96 sebelum edukasi dan setelah edukasi naik menjadi 75,88. Terdapat pengaruh pemberian edukasi gizi online terhadap peningkatan pengetahuan kesehatan dan gizi satpam.